Emergence of Resistant Escherichia coli Mutants in Microfluidic On-Chip Antibiotic Gradients - Nagy, Krisztina; Dukic, Barbara; Hodula, Orsolya; Ábrahám, Ágnes; Csákvári, Eszter; Dér, László; Wetherington, Miles T.; Noorlag, Janneke; Keymer, Juan E.; Galajda, Péter (Frontiers in Microbiology, 2022)
Spatiotemporal structures and heterogeneities are common in natural habitats, yet their role in the evolution of antibiotic resistance is still to be uncovered. We applied a microfluidic gradient generator device to study the emergence of resistant bacteria in spatial ciprofloxacin gradients. We observed biofilm formation in regions with sub-inhibitory concentrations of antibiotics, which quickly expanded into the high antibiotic regions. In the absence of an explicit structure of the habitat, this multicellular formation led to a spatial structure of the population with local competition and limited migration. Therefore, such structures can function as amplifiers of selection and aid the spread of beneficial mutations. We found that the physical environment itself induces stress-related mutations that later prove beneficial when cells are exposed to antibiotics. This shift in function suggests that exaptation occurs in such experimental scenarios. The above two processes pave the way for the subsequent emergence of highly resistant specific mutations.